PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 KOTO SALAK - Rinaldo, Oga (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical problem-solving proficiency serves as a pivotal learning objective within the realm of mathematics that students are required to attain. Nonetheless, the preliminary assessment results on mathematical problem-solving skills at SMPN 1 Koto Salak indicate that students are encountering challenges in effectively resolving such problems. An approach to address this issue involves the implementation of the Problem Based Learning (PBL) instructional model. The primary objective of this study is to determine and outline whether there exists a superiority in the mathematical problem-solving skills of students who are exposed to Problem Based Learning compared to those who receive conventional classroom teaching in the eighth grade at SMP Negeri 1 Koto Salak in the academic period of 2023/2024. This particular study adopts a quasi-experimental design with Randomized Control Group Only Design. The study's target population consists of eighth-grade students at SMPN 1 Koto Salak in the academic year 2023/2024. Sampling procedures were carried out employing a random sampling technique, with class VIII A designated as the experimental group and class VIII B as the control group. The assessment tool employed is a mathematical problem-solving test comprising essay questions. Examination of the final test data reveals a P-value of 0.000 with a significance level (α) of 0.05. Given that the P-value is less than α, the null hypothesis (H0) is rejected. Consequently, it can be inferred that students exposed to the Problem Based Learning model demonstrate superior mathematical problem-solving abilities compared to those undergoing conventional instruction in eighth grade at SMP Negeri 1 Koto Salak.Keywords– Problem Based Learning, Mathematical Problem Solving Ability